If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 49 + -3x = 34 + -2x Solving 49 + -3x = 34 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. 49 + -3x + 2x = 34 + -2x + 2x Combine like terms: -3x + 2x = -1x 49 + -1x = 34 + -2x + 2x Combine like terms: -2x + 2x = 0 49 + -1x = 34 + 0 49 + -1x = 34 Add '-49' to each side of the equation. 49 + -49 + -1x = 34 + -49 Combine like terms: 49 + -49 = 0 0 + -1x = 34 + -49 -1x = 34 + -49 Combine like terms: 34 + -49 = -15 -1x = -15 Divide each side by '-1'. x = 15 Simplifying x = 15
| 1.3x+-13=-5.2 | | 2c+4+3c=-36 | | 5x+15=22 | | 49-3x=3x-5 | | 7x-28=-14 | | 4(x+2)+x-11=2x-3+3(x+4) | | -3(9c+8)=26 | | (A+2)0.78=3.9 | | 4(90-x)+2=(180-x)+8 | | C=X^2-15x+50 | | 3(x+5)=x-10 | | 3535x-5725x+58y=4734z | | a/4-3/4=1/3 | | y^2-12y+27= | | X^5-4x^4+7x^3-10x^2+10x-4=0 | | A=(7x)(3x) | | -7x-3=13 | | 9.5=0.4(5x)+2.5 | | 9x+1=5x+15 | | 7*y-3=2*y-3 | | x^2-10x+25=x^2-8x+16+1 | | (x-5)=(x-4) | | 10(2x-10)=0 | | 3*200=2+x | | ln(x+8)-ln(x-2)=ln(x+2) | | h=-16t^2+250 | | a-1=14 | | 2x-5=8x+7-4x | | 4(2z+1)-6=70 | | x^2-10x+25-1=0 | | 24x+3=51 | | 12x+6y=8 |